2013
DOI: 10.1021/mp400482a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Chelating 2-Hydroxyphenyl Amide Pharmacophore for Inhibition of Influenza Virus Endonuclease

Abstract: The influenza virus PA endonuclease is an attractive target for development of novel anti-influenza virus therapeutics. Reported PA inhibitors chelate the divalent metal ion(s) in the enzyme's catalytic site, which is located in the N-terminal part of PA (PA-Nter). In this work, a series of 2-hydroxybenzamide-based compounds have been synthesized and biologically evaluated in order to identify the essential pharmacophoric motif, which could be involved in functional sequestration of the metal ions (probably Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…However, with the availability of effective endonuclease assays and high resolution crystal structures, there have been numerous reports of novel chemotypes that inhibit this enzyme and an upsurge in accompanying medicinal chemistry (43)(44)(45)(46). Our studies have revealed some of the structural origins of how resistance can emerge, and this information can now guide medicinal chemists in their optimization of new inhibitor scaffolds and prioritization of early lead compounds.…”
Section: Discussionmentioning
confidence: 86%
“…However, with the availability of effective endonuclease assays and high resolution crystal structures, there have been numerous reports of novel chemotypes that inhibit this enzyme and an upsurge in accompanying medicinal chemistry (43)(44)(45)(46). Our studies have revealed some of the structural origins of how resistance can emerge, and this information can now guide medicinal chemists in their optimization of new inhibitor scaffolds and prioritization of early lead compounds.…”
Section: Discussionmentioning
confidence: 86%
“…This enzymatic endonuclease activity assay was performed according to a previously published method (Carcelli et al, 2014) with minor modifications. One microgram of recombinant PA-Nter was incubated with 1 mg (16.7 nM) of singlestranded circular DNA plasmid M13mp18 (Bayou Biolabs, Metairie, Louisiana) in the presence of the test compounds and at a final volume of 25 ml.…”
Section: Methodsmentioning
confidence: 99%
“…PA endonuclease inhibitors, including the 4-substituted 2,4-dioxobutanoic acid derivatives (29,30) and the substituted 2,6-diketopiperazine natural product flutimide (31,32), were characterized 2 decades ago in enzymatic, cell-based, and limited in vivo assays (29), where they demonstrated potent (micromolar 50% inhibitory concentrations [IC 50 s]) and cap-dependent inhibition of influenza A and B viruses. Subsequently, marchantins, catechins (33,34), hydroxamic acid and N-hydroxyimides (35,36), 3-hydroxypyridin-2(1H)-one derivatives (37, 38), 3-hydroxyquinolin-2(1H)-one derivatives (39), fullerene derivatives (40), and carboxamide derivatives (41) were identified as PA protein inhibitors. In many of these studies, a library of compound derivatives was screened with a limited number of influenza viruses and/or assays, making it difficult to compare the reported efficacies accurately (42).…”
mentioning
confidence: 99%